2019
DOI: 10.3390/f10050371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Litter Quality on Needle Decomposition for Four Pine Species in Korea

Abstract: Litter decomposition involves multiple complex processes, including interactions between the physicochemical characteristics of litter species and various environmental factors. We selected four representative pine species in South Korea (Pinus densiflora Siebold & Zucc., Pinus thunbergii Parl., Pinus koraiensis Siebold & Zucc., and Pinus rigida Miller) to investigate the decay rate and effects of the physicochemical properties on decomposition. Needle litters were incubated in microcosms at 23 °C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…2f), suggesting that litter physical traits play important roles in controlling litter decomposition. Our ndings con rm some previous observations (Chae et al 2019;Cornelissen et al 1999;Makkonen et al 2012). Furthermore, we found that water saturation capacity was the best physical predictor and contributed 9.7% relative importance for litter decomposition ( Table 2).…”
Section: Importance Of Initial Litter Traits In Controlling Decomposisupporting
confidence: 91%
See 2 more Smart Citations
“…2f), suggesting that litter physical traits play important roles in controlling litter decomposition. Our ndings con rm some previous observations (Chae et al 2019;Cornelissen et al 1999;Makkonen et al 2012). Furthermore, we found that water saturation capacity was the best physical predictor and contributed 9.7% relative importance for litter decomposition ( Table 2).…”
Section: Importance Of Initial Litter Traits In Controlling Decomposisupporting
confidence: 91%
“…Besides litter chemical traits, litter physical traits could also directly or indirectly in uence the decomposition process (Chae et al 2019;Kurokawa and Nakashizuka 2008). Several studies have focused on the role of physical traits in controlling litter decomposition, especially at the rst stage of decomposition (Pakeman et al 2011;Quested et al 2007;Makkonen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, based on the research in Korea during the ten-weeks decomposition of leaves, pine needles reduced mass was only 23.6%-30.4% (Chae et al, 2019). It shows that the pine litter needs a long time to decompose.…”
Section: Resultsmentioning
confidence: 98%
“…These unfavourable conditions combined with changes in litter quality and quantity allow the rapid disappearance of any new surface litter. Litter with high quality (low C/N or lignin/N) has faster decomposition rates compared to low litter quality (high C/N or lignin/N) (Chae et al 2019). Faster litter decomposition combined with a lower root density and turnover could reduce the organic matter (Hairiah et al 2006), and lead to anthropogenic soil degradation (Lal 2015).…”
Section: Introductionmentioning
confidence: 99%